18.2k views
0 votes
For f(x) = 2x+1 and g(x) = x² -7, find (ƒ-g)(x).​

For f(x) = 2x+1 and g(x) = x² -7, find (ƒ-g)(x).​-example-1

2 Answers

10 votes

Answer:

A

Explanation:

(f - g)(x)

= f(x) - g(x)

= 2x + 1 - (x² - 7) ← distribute parenthesis by - 1

= 2x + 1 - x² + 7 ← collect like terms

= - x² + 2x + 8

User Nerdlyist
by
5.5k points
2 votes

Answer:

-x2 + 2x + 8

Explanation:

Your first step will be to set up the problem:

f(x) - g(x)

Next, you will substitute in your values:

(2x + 1) - (x2 - 7)

The easiest way to do the subtraction problems is to distribute your negative into your second set of parenthesis, so your expression would become:

2x + 1 - x2 + 7

Then combine your like terms:

2x - x2 + 8

Lastly, put your expression in standard form (highest exponent to lowest)

-x2 + 2x + 8

User Dilsingi
by
6.1k points